Location of triangular equilibrium points in the perturbed CR3BP with laser radiation pressure and oblateness - Khalifa, Nabawia (International Journal of Advanced Astronomy, 2018)
This paper represents a semi-analytical study of the effect of ground-based laser radiation pressure on the location of triangular points in the framework of the planar circular restricted three-body problem (CR3BP). The formulation includes both the effects of oblateness of J2 in addition to laser radiation pressure, where laser’s disturbing function expanded in Legendre polynomials up to the first order. Earth-Moon system is considered in which a laser station is located on Earth and sends laser beams toward the infinitesimal body. The model takes into account the effect of Earth's atmosphere on laser beam propagation. The numerical application emphasis that the location of the triangular points affected by the considered perturbations.